Vivianite scaling in wastewater treatment plants: Occurrence, formation mechanisms and mitigation solutions. (1st June 2021) - Prot, T.; Korving, L.; Dugulan, A.I.; Goubitz, K.; van Loosdrecht, M.C.M.
Highlights: Vivianite scaling is widely occurring in WWTPs even though it is rarely reported. Iron reduction appears to be the cause of vivianite scaling in anaerobic equipment. pH increase is the main trigger for scaling around centrifuges treating raw sludge. Solubility of vivianite decreases when T >32 °C, favoring scaling in heat exchangers. Proper sludge admixing and fe dosing are essential to mitigate vivianite scaling. Abstract: The presence of soluble iron and phosphorus in wastewater sludge can lead to vivianite scaling. This problem is not often reported in literature, most likely due to the difficult identification and quantification of this mineral. It is usually present as a hard and blue deposit that can also be brown or black depending on its composition and location. From samples and information gathered in 14 wastewater treatment plants worldwide, it became clear that vivianite scaling is common and can cause operational issues. Vivianite scaling mainly occurred in 3 zones, for which formation hypotheses were discussed. Firstly, iron reduction seems to be the trigger for scaling in anaerobic zones like sludge pipes, mainly after sludge thickening. Secondly, pH increase was evaluated to be the major cause for the formation of a mixed scaling (a majority of oxidized vivianite with some iron hydroxides) around dewatering centrifuges of undigested sludge. Thirdly, the temperature dependence of vivianite solubility appears to be the driver for vivianite deposition in heat exchanger around mesophilic digesters (37 °C), while higher temperatures potentially aggravate the phenomenon, for instance in thermophilic digesters. Mitigation solutions like the use of buffer tanks or steam injections are discussed. Finally, best practices for safe mixing of sludges with each other are proposed, since poor admixing can contribute to scaling aggravation. The relevance of this study lays in the occurrence of ironphosphate scaling, while the use of iron coagulants will probably increase in the future to meet more stringent phosphorus discharge limits. Graphical abstract: Image, graphical abstract